KAJIAN HUKUM PERSAINGAN USAHA DALAM MEDIA MASSA (Tinjauan Aspek Kemerdekaan Pers dan UU No. 40 Tahun 1999 tentang Pers) - Naungan Harahap (Jurnal Media Justitia Nusantara, 2015)
An unhealthy competition phenomenon among national mass media actors in reform era to be more transparence even it has been implemented by dishonesty and damaging public. The situation results inany problems and concern between press idealism and commercial aspects. An implementation of press independency is harmful. It is a consequence of application Act No. 40 of1999 on press introducing mass media serving as the economic institution. It expected that the concerned parties in media business, press idealism and independency must consider an equal principle and fairness. Because the economic function could be a boomerang to the press. When the capital owner has much intervention to the editorial staff, it has been mad press partiality. Whereas it is represent the press independency, especially in upright the justice and truth.